Archaeology of disaster in Indonesia: where are we now? - Truman Simanjuntak; Marlon Ririmasse (Berita Sedimentologi, 2021)
Natural disasters are a phenomenon that shaped the Indonesian Archipelago. Earthquakes and volcanic activities have become periodic experiences in the lives of people in this region. The geographical characteristics of Indonesia which are located at the confluence of active plates and part of the global volcanic chain are natural factors that make these islands vulnerable to disasters. Cultural historical studies have recorded various phenomena of past natural disasters in the archipelago. Some have had minimal impact, but others have resulted in the loss of civilization. Although the issue has become the important part of the civilization and profile of Indonesia, the archaeological study of disasters has not well developed. The existing studies so far are still very partial with the fragmentary results. Characterized with this complex character, the study of archaeological disaster requires a multidisciplinary approach. This paper attempts to discuss the archaeology of disasters in Indonesia including the background, current conditions and the prospects of future development. Particularly in discussing the role of local wisdoms in dealing with disasters as part of the civilization of the archipelago.